2020
DOI: 10.1007/s41042-020-00037-5
|View full text |Cite
|
Sign up to set email alerts
|

Positive Emotions as a Potential Mediator of a Multi-Component Positive Psychology Intervention Aimed at Increasing Mental Well-Being and Resilience

Abstract: We examined mediators of a multi-component positive psychology intervention for healthy employees. We analyzed data from a randomized controlled trial involving 158 participants who were assigned to a six-session intervention program or a wait-list control group. In total, 144 participants completed baseline and post-test assessment. The mediating effects of positive emotions and psychological flexibility on treatment outcomes mental well-being and resilience at post-test assessment were examined. We also exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 84 publications
1
5
0
Order By: Relevance
“…The function of positive emotions as a potential mediator of wellbeing has been strongly suggested in several models (Hendriks et al, 2021). In the positive-activity model, the association between the performance of positive activity and well-being may appear transparent with the intervention of positive emotions (Lyubomirsky & Layous, 2013).…”
Section: Positive Emotionmentioning
confidence: 99%
See 1 more Smart Citation
“…The function of positive emotions as a potential mediator of wellbeing has been strongly suggested in several models (Hendriks et al, 2021). In the positive-activity model, the association between the performance of positive activity and well-being may appear transparent with the intervention of positive emotions (Lyubomirsky & Layous, 2013).…”
Section: Positive Emotionmentioning
confidence: 99%
“…Happier individuals are the result of the complex interplay between their positive emotions, positive behaviours, positive thoughts, and need satisfaction as stimulated by their conscious positive activities (Lyubomirsky & Layous, 2013). Hence, enhancing positive emotions is central if positive changes in the ability to manage mental well-being and life challenges are to be gained (Hendriks et al, 2021). As such, studies involving PP interventions and mental well-being have also recognized positive emotions as a possible mediating variable (Li et al, 2017;Schiffrin, 2014).…”
Section: Positive Emotionmentioning
confidence: 99%
“…In addition, some activities might be more easy to integrate in daily life and thereby be more effective (e.g., self-focused kindness), while other behaviors might be more effective by putting in greater effort (e.g., other-focused kindness; Schiffer and Roberts, 2018 ). Furthermore, where positive emotions might be an important underlying mechanism of positive psychological interventions in general and of acts of kindness in particular (Nelson et al, 2016 ; Hendriks et al, 2020 ), the type of emotions that influence well-being might differ per kindness type. For example, self-focused kindness might elicit low-arousal positive emotions such as relaxation and satisfaction, while other-focused kindness might elicit high-arousal positive emotions such as joy, happiness, and surprise.…”
Section: Discussionmentioning
confidence: 99%
“…One previous study inves�ga�ng an email-guided MPPI showed that posi�ve rela�ons and self-compassion may mediate the effect on wellbeing (Schotanus-Dijkstra et al, 2017). Another study of a MPPI, were healthy employees focused on exploring posi�ve emo�ons, doing new ac�vi�es, reframing nega�ve thoughts, and adop�ng an adap�ve mind-set, showed that improvements in wellbeing were possibly mediated through posi�ve emo�ons (Hendriks et al, 2020). Furthermore, one recent study also exploring mechanisms, documented how a MMPI for adolescents may have worked through changing the connec�on between different dimensions (wellbeing and psychological distress) of mental health (Tejada-Gallardo et al, 2022).…”
Section: Effectiveness and Mechanisms Of Change In Mmpismentioning
confidence: 99%